CONSUMER BEHAVIOR OF CHINESE TOURISTS Case: Santa Claus Village, Rovaniemi - Ngo, Ngoc Lan Anh Jr (2019)
The aim of this thesis research was to discuss the travel motivations and consumer behaviour of Chinese tourists and its impacts on Santa Claus Village and Rovaniemi, Finland. This case study made an effort to understand Chinese tourists’ perceptions on Santa Claus Village products and services. The theoretical framework of this paper includes three main themes, which are the tourism operating environment in Rovaniemi, Chinese market and media behaviour of Chinese tourists. Nova Skyland Hotel is the commissioner of this thesis research. The hotel is located inside Santa Claus Village area in Rovaniemi, Finland. The role of the commissioner is to support the progress of establishing related materials about Santa Claus Village as well as conducting the survey. This thesis work introduces several concepts related to Rovaniemi and Chinese travellers such as tourism, Chinese tourism market and media behaviour of Chinese tourists. A quantitative research method was implemented during the process. Findings related to the thesis were collected through an electronic survey. The survey was handed out during February to late March 2019. Accordingly, the results show the importance in creating unique and memorable products as well as services in Santa Claus Village. Therefore, the results can be used in obtaining Chinese tourists’ perceptions through their background, what elements that drive them to travel and how they see Santa Claus Village as a tourist attraction. The study helps organizations understand and develop the destination to meet the needs and satisfaction of Chinese visitors.